KARAKTERISTIK KONTEN YOUTUBE SEBAGAI OBJEK JAMINAN UTANG DI BANK - Abdul Hafid Firdaus; Dyah Ochtorina Susanti; Galuh Puspaningrum (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2023)
This research aims to understand the characteristics of Youtube content as an object of collateral for debts at banks, the ratification of Government Regulation Number 24 of 2022 concerning Implementing Regulations of Law Number 24 of 2019 concerning the Creative Economy, Youtube content as another form of copyright in accordance with Article 40. Law Number 28 of 2014 can be used as an object of fiduciary guarantee. However, there are no specific regulations governing Youtube content or copyright as an object of fiduciary guarantee, so the main basis for the object of fiduciary guarantee is Law Number 42 of 1999 concerning Guarantees, making financial institutions doubtful about providing credit. with Youtube content objects as collateral due to the lack of clarity in regulations, both in terms of valuation and execution. This research uses Normative Legal Research with a statutory, comparative and conceptual approach. This research seeks to provide an explanation and understanding of the characteristics of Youtube content intended by law as an object of collateral in banks.